A consumer-based smart home and health monitoring system. (2018) - Patil, Kailas; Laad, Meena; Kamble, Aakash; Laad, Shivani
Past few decades have seen a sharp increase in air pollution and its harmful effects on human health. Indoor air quality is a major determining factor of personal exposure to pollutants in today's scenario. Major time is spent in indoor environments by a majority of people. Therefore monitoring indoor air quality has become an important issue. There are various reasons for poor quality of indoor air in which the oxygen level is below the healthy level such as influx of polluted outdoor air, geological materials around the residential properties, household activities such as cooking, cleaning, smoking, materials used in construction or painting the house etc. With increasing pollution, the respiratory diseases are on the rise and therefore there is a strong need to develop a smart home system which is capable to monitor healthy environmental conditions for its users. This research study proposes a smart system that uses a renewable source of energy, monitors and controls the overall power consumption of the home, and keeps a check on the healthy environmental conditions by measuring the level of oxygen and provides a provision for an alarm when the oxygen level falls below the safe limit. The proposed model is compact, cost-effective, energy-efficient and provides a health-smart home system to the consumer and is especially useful for the old and physically challenged.